(untitled) (Faridpur Medical College Journal, 2015)
This cross sectional and observational study was conducted in the Department of Microbiology, Sylhet MAG Osmani Medical College, Sylhet, during the period from 1st January 2012 to 31st December 2012 with a view to explore the seropositivity of Hepatitis G virus (HGV) in blood donors, pregnant women, new born and apparently healthy subjects. For this purpose 45 blood donors, 45 pregnant women, 45 new born babies of same mothers and 45 apparently healthy subjects were selected according to the inclusion and exclusion criteria. The HGV antibody was measured in venous blood from blood donor, pregnant women and apparently healthy subjects; and cord blood from newborn babies with a commercially available enzyme-linked immunosorbent assay (ELISA) method. The mean age of the blood donors, pregnant women and healthy subjects was 24.9 (SD ± 3.5) years; 24.9 (SD ± 3.5) years and 22.1 (SD ± 1.5) years respectively. The overall seropositivity of HGV was 3 (1.7%). The seropostivity of HGV of blood donors, new born babies and healthy subjects was 1 (2.2%) in each group but no HGV antibody positivity among the pregnant women (p=0.797). Among the male patients 2 (2.2%) patients were seropositive for HGV; while in female patients, 1 (1.1%) patient was seropositive for HGV (p=0.547). Among the patients with previous blood transfusion 1 (1.9%) patient was seropositive for HGV; while among patients without previous blood transfusion 2 (1.6%) patients were seropositive for HGV (p=0.882). This study yielded that there is high prevalence of HGV seropositivity among population in this region of Bangladesh. So, screening of blood units for HGV would deserve consideration. Faridpur Med. Coll. J. 2014;9(1): 28-31